Tumour microenvironment on mitochondrial dynamics and chemoresistance in cancer. (2nd December 2018) - Han, Youngjin; Cho, Untack; Kim, Soochi; Park, In Sil; Cho, Jae Hyun; Dhanasekaran, Danny N.; Song, Yong Sang
Abstract: Mitochondria, evolutionally acquired symbionts of eukaryotic cells, are essential cytoplasmic organelles. They are structurally dynamic organelles that continually go through fission and fusion processes in response to various stimuli. Tumour tissue is composed of not just cancer cells but also various cell types like fibroblasts, mesenchymal stem and immune cells. Mitochondrial dynamics of cancer cells has been shown to be significantly affected by features of tumour microenvironment such as hypoxia, inflammation and energy deprivation. The interactions of cancer cells with tumour microenvironment like hypoxia give rise to the inter- and intratumoural heterogeneity, causing chemoresistance. In this review, we will focus on the chemoresistance by tumoural heterogeneity in relation to mitochondrial dynamics of cancer cells. Recent findings in molecular mechanisms involved in the control of mitochondrial dynamics as well as the impact of mitochondrial dynamics on drug sensitivity in cancer are highlighted in the current review.